(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
This paper explores how literary representations of the self are reshaped in light of cybersecurity. In a digital era where writing is subject to algorithmic control and surveillance, literature becomes a site of negotiation between identity and technology. The study examines how contemporary narratives reflect or resist digital mechanisms that encode, monitor, and regulate subjectivity. By situating the literary self within cybernetic systems and post-digital environments, the article highlights how authorship, freedom, and authenticity are reconfigured. Ultimately, literature emerges as a strategic space that challenges data-driven power and asserts virtual autonomy.